Implementation of The Kauny Method Using The ADLX -Introflex Approach to Improve The Quality of Tahfidz Learning Based on Digitalization at SD-IT Hafizul Ilmi - Artati, Artati; Akmaluddin, Akmaluddin; Sari, Siti Mayang (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
The current phenomenon is that students do not yet have a deep interest in memorizing the Quran, and their talent for memorizing is still simple. So far, teachers only give directions and memorize assignments, and students must memorize verses of the Al-Qur'an and their meanings and interpret these verses. This phenomenon greatly worsens students' interest in learning; rote learning becomes very unpleasant for students. Implementing the Kauny method with the ADLX/Introflex approach can improve the quality of tahfiz learning, especially memorization based on digitalization. Students will be more interested in reading and interpreting it using hand movements and gesture language, so interpreting the meaning of verses will be easier and more enjoyable. They can memorize well and completely according to their experience. The aim of this research is: Students can activate their memory through memorizing and reading tahfiz and kauny methods with the ADLX/INTROFLEX approach. ADLX, or the Active Deep Learner experience learning approach, is a learning approach that combines active learning and deep learning approaches. The research method used is descriptive qualitative, using research instruments with interviews, documentation, and rote-based evaluations. The qualitative descriptive research method is a type, design, or research plan that is usually used to examine research objects that are natural or in real conditions and are not set up as in experiments. The research results from several sources show that implementing the Kauny method with the ADLX/Introflex approach is a very enjoyable tahfiz learning method. Student learning outcomes increase by gaining valuable experience and enjoyable learning. This method can even be applied to ABK students. Through its implementation, the quality of education in elementary schools increases because it provides students with experience in memorizing the Qur'an.